Case Report: Efficacy and safety of dose-escalated Mazdutide, a GLP-1/GCGR dual agonist, in an adolescent with obesity, type 2 diabetes, and hyperuricemia - Cheng, Wenfei; Chen, Zilong; Li, Puyu; Zhang, Yingyu; Ma, Yujin; Liu, Peng; Jiang, Hongwei (Frontiers in Endocrinology, 2025)
ObjectiveMazdutide, a glucagon-like peptide-1/glucagon receptor (GLP - 1/GCGR) dual agonist, has shown marked efficacy in glycemic control, weight loss, and metabolic improvement in adults. However, data in adolescents remain limited. This report explores its therapeutic potential in an adolescent with obesity-related type 2 diabetes mellitus (T2DM) and hyperuricemia (HUA).Study design and methodsWe report the case of a 15-year-old male patient diagnosed with obesity (BMI: 30.64 kg/m²), type 2 diabetes mellitus (HbA1c: 9.60%), and hyperuricemia (serum uric acid: 511 μmol/L). The patient underwent a dose-escalation regimen of Mazdutide (2 mg → 4 mg → 6 mg, administered subcutaneously once weekly) in combination with metformin and insulin to evaluate therapeutic efficacy and safety outcomes.ResultsAfter 36 weeks, the patient showed significant improvement: weight decreased by 16.8 kg (18.89% BMI reduction), uric acid dropped by 37.00%, and HbA1c fell by 21.88%. No hypoglycemic episodes occurred. Lipid levels improved notably: triglycerides fell by 69.02%, total cholesterol by 13.65%, and LDL cholesterol by 17.27%. Hepatic steatosis resolved by week 14, as confirmed by ultrasound. No adverse events were reported, and benefits were sustained post-treatment.ConclusionsMazdutide exhibited robust metabolic efficacy and good tolerability in an adolescent with obesity, T2DM, and HUA. It improved glycemic control, reduced weight and uric acid, reversed steatosis, and modulated lipid profiles. These findings support its potential as a comprehensive treatment for adolescent metabolic disorders.